2021
DOI: 10.1007/s00419-021-01882-9
|View full text |Cite
|
Sign up to set email alerts
|

Large deformation behavior of functionally graded porous curved beams in thermal environment

Abstract: The in-plane thermoelastic response of curved beams made of porous materials with different types of functionally graded (FG) porosity is studied in this research contribution. Nonlinear governing equations are derived based on the first-order shear deformation theory along with the nonlinear Green strains. The nonlinear governing equations are solved by the aid of the Rayleigh–Ritz method along with the Newton–Raphson method. The modified rule-of-mixture is employed to derive the material properties of imperf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…As already described, two porosity distribution patterns, namely even and logarithmic-uneven, were considered for this study. Accordingly, the corresponding values of elastic modulus, mass density, and Poisson's ratio based on the rule of mixture are described as [69] Even porosity dispersion:…”
Section: Equations Of Motionmentioning
confidence: 99%
“…As already described, two porosity distribution patterns, namely even and logarithmic-uneven, were considered for this study. Accordingly, the corresponding values of elastic modulus, mass density, and Poisson's ratio based on the rule of mixture are described as [69] Even porosity dispersion:…”
Section: Equations Of Motionmentioning
confidence: 99%
“…Lu et al 101 revealed the buckling of clamped FG arches under the locally distributed radial force. The stability of the FG porous curved beams under the thermal loading is studied by Nikrad et al 102 The snap-buckling and resonance response of FG graphene platelets reinforced composites fixed supported curved beams considering temperature changes and elastic foundations were studied by Zhang et al 103 Yang et al 104 discussed the size-dependent nonlinear in-plane thermomechanical stability of clamped FG multilayer shallow arches. Mohamed et al 105 identified the optimal design parameters for helicoidal laminated composite curved beam that maximized the lateral limit load and minimized the extent of bi-stability.…”
Section: Introductionmentioning
confidence: 99%
“…Penna et al (2021) presented the bending response of FG porous Bernoulli-Euler nano-beams under hygro-thermo-mechanical force. Nikrad et al (2021) displayed FG porous curved beams with different cases of porosity by using the firstorder shear deformation theory with the nonlinear Green strains. Moreover, a lot of researchers discuss the porosity properties of functionally graded materials.…”
Section: Introductionmentioning
confidence: 99%